Social Media Marketing and Customer Retention of Selected Small and Medium Enterprises (SMEs) In South-West Nigeria - ADEJUWON, Joshua Adewale; LAWAL, Lateefat O (International Journal Of Management And Economics Invention, 2022)
The purpose of this study is to examine the effect of the adoption of social media marketing (SMM) by SMEs on the ability to retain customers over the years through the SMM components which include customer engagement, branded entertainment, E word of mouth, social interaction and customization. The study adopted descriptive survey research design. The population used in this study comprises of the SMEs in Lagos, Oyo and Osun States as these states have the largest concentration of SMEs in Southwest, Nigeria. The sample size of 489 was determined using the Raosoft Sample Size calculator. Theprimary source of data collection (questionnaire)was adopted. Reliability test of the questionnaire was carried out and the Cronbach alpha coefficient was 0.889. Data were analysed using descriptive and inferential statistics (Statistical Package for Social Sciences (SPSS) version 24 and SmartPLS version 3.3.3). The PLS-SEM results revealed that at 95% confidence level, customer engagement (β = 0.366, t= 2.671), customization (β = 0.356, t= 2.679) and social interaction (β = 0.255, t= 2.154) are significant however, branded entertainment (β = -0.047, t= 0.281), and E-Word of mouth (β = -0.024, t=0.163) are statistically insignificant. This study concludes that social media marketing significantly affects customer retention of SMEs in Southwest Nigeria, hence, it is recommended thatSMEs managers/owners should focus more on customer engagement, customization and social interaction in order to enhance customer retention.